A history of the Islamic world, 600-1800 : empire, dynastic formations, and heterogeneities in pre-modern Islamic West-Asia /: empire, dynastic formations, and heterogeneities in pre-modern Islamic West-Asia. (2020) - Steenbergen, J. van
No abstract available